Glass substrate manufacturing method
By setting a strain point of 690 to 750°C and a controlled cooling rate, the method reduces thermal shrinkage in glass substrates, addressing pattern misalignment and equipment wear in high-definition display manufacturing.
Patent Information
- Application Number
- JP2021527493
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-18
- Filing Date
- 2020-05-22
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-05-22
AI Technical Summary
Existing glass substrates for high-definition displays face issues with thermal shrinkage during heat treatment, leading to pattern misalignment and equipment wear, while maintaining a high strain point to reduce shrinkage increases molding temperatures and shortens equipment life.
A method for manufacturing glass substrates with a strain point of 690 to 750°C and a controlled cooling rate of 100 to 400°C/min, reducing thermal shrinkage to 15 ppm or less by adjusting the glass composition and cooling process.
The method effectively minimizes dimensional changes during heat treatment, preventing equipment wear and maintaining production efficiency by balancing strain point and cooling rate.
Smart Images

Figure 0007610187000003 
Figure 0007610187000001 
Figure 0007610187000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a glass substrate, specifically, to a method for manufacturing a glass substrate suitable for organic light-emitting diode (OLED) displays and liquid crystal displays, and further to a method for manufacturing a glass substrate suitable for oxide TFT and low-temperature p-Si TFT (LTPS) driven displays. [Background technology]
[0002] Glass substrates have been widely used for flat panel displays such as liquid crystal displays, hard disks, filters, sensors, etc. In recent years, in addition to conventional liquid crystal displays, OLED displays have been actively developed due to their self-luminescence, high color reproducibility, wide viewing angle, high-speed response, high definition, etc., and some of them have already been put to practical use.
[0003] In addition, the LCD and OLED displays of mobile devices such as smartphones need to display a lot of information in a small area, so they require ultra-high definition screens.Furthermore, they also need high-speed response to display moving images.
[0004] For such applications, OLED displays or liquid crystal displays driven by LTPS are suitable. OLED displays emit light when a current flows through the OLED elements that make up the pixels. For this reason, materials with low resistance and high electron mobility are used as the driving TFT elements. In addition to the above-mentioned LTPS, oxide TFTs such as IGZO (indium, gallium, zinc oxide) have been attracting attention as such materials. Oxide TFTs have low resistance and high mobility, and can be formed at relatively low temperatures. In addition, oxide TFTs have excellent uniformity in TFT characteristics when forming elements on a large-area glass substrate, so they have attracted attention as a promising TFT forming material, and some of them have already been put to practical use.
[0005] Glass substrates used in high-definition displays are required to have many properties. In particular, the following properties (1) and (2) are required:
[0006] (1) If the glass contains a large amount of alkaline components, alkaline ions will diffuse into the semiconductor material during heat treatment, causing deterioration of the film properties. Therefore, the content of alkaline components (especially Li and Na components) must be low or substantially absent.
[0007] (2) In processes such as film formation, dehydrogenation, crystallization of the semiconductor layer, and annealing, the glass substrate is heat-treated at several hundred degrees Celsius. Problems that can occur during heat treatment include pattern misalignment caused by thermal shrinkage of the glass substrate. The higher the resolution of the display, the higher the heat treatment temperature, but conversely, the smaller the tolerance for pattern misalignment. Therefore, glass substrates are required to have small dimensional changes during heat treatment. The main causes of dimensional changes during heat treatment are thermal shrinkage and film stress after film formation. Therefore, in order to minimize dimensional changes during heat treatment, a high strain point is required.
[0008] Furthermore, from the viewpoint of manufacturing the glass substrate, the glass substrate is required to have the following properties (3) to (5). (3) The molding temperature is low to extend the life of the molding equipment. (4) It must have excellent melting properties to prevent melting defects such as bubbles, bumps, and striae. (5) Excellent resistance to devitrification in order to prevent inclusion of devitrification crystals in the glass substrate. Summary of the Invention [Problem to be solved by the invention]
[0009] One approach to reducing the thermal shrinkage is to design the strain point to be high, as described above. However, if the strain point is too high, the melting temperature and molding temperature will increase, which has the disadvantage of shortening the life of the melting equipment and molding equipment.
[0010] The present invention has been made in view of the above circumstances, and its technical object is to provide a method for manufacturing a glass substrate capable of reducing dimensional changes during heat treatment while avoiding a shortened life of equipment. [Means for solving the problem]
[0011] As a result of intensive research, the present inventors have found that by controlling the strain point of the glass substrate and the cooling rate during molding within a predetermined range, the thermal shrinkage rate can be reduced to a desired value while reducing the burden on the manufacturing equipment, and propose this as the present invention. That is, the manufacturing method of the glass substrate of the present invention is a method for manufacturing a glass substrate having a strain point of 690 to 750°C by melting and molding a glass raw material, and is characterized in that, by setting the average cooling rate in the temperature range from (annealing point + 150°C) to (annealing point - 200°C) in the cooling process during molding to 100 to 400°C / min, a glass substrate having a thermal shrinkage rate of 15 ppm or less when heat-treated at 500°C for 1 hour is obtained. Here, the "strain point" and "annealing point" refer to values measured based on the method of ASTM C336. The "thermal shrinkage rate when heat-treated at 500°C for 1 hour" is measured by the following method. First, as shown in FIG. 1(a), a rectangular sample G of 160 mm x 30 mm is prepared as a measurement sample. Markings M are formed at both ends of the long side of the rectangular sample G at positions 20 to 40 mm away from the edge using #1000 waterproof abrasive paper. Then, as shown in FIG. 1(b), the rectangular sample G on which markings M are formed is folded in two along the direction perpendicular to the markings M to produce sample pieces Ga and Gb. Then, only one of the sample pieces Gb is heated from room temperature to 500° C. at a rate of 5° C. / min, held at 500° C. for 1 hour, and then cooled at a rate of 5° C. / min for heat treatment. After the heat treatment, as shown in FIG. 1(c), the sample piece Ga that has not been heat-treated and the sample piece Gb that has been heat-treated are arranged in parallel, and the positional deviations (ΔL1, ΔL2) of the markings M of the two sample pieces Ga and Gb are read by a laser microscope, and the thermal shrinkage is calculated by the following formula. In the following formula, 10 mm is the distance between the initial markings M. "Average cooling rate" refers to the speed calculated by calculating the time it takes for the central part of the glass in the width direction to pass through an area (annealing area) in the temperature range from (annealing point + 150°C) to (annealing point - 200°C), and dividing the temperature difference within the annealing area (= 350°C) by the time required to pass through.
[0012] Heat shrinkage rate (ppm)=[{ΔL1(μm)+ΔL2(μm)}×10 3 ] / l0(mm)
[0013] In the method for producing the glass substrate of the present invention, the glass substrate is preferably formed by an overflow downdraw method.
[0014] The method for producing a glass substrate of the present invention preferably produces a glass substrate having a width of 3 m or more.
[0015] The method for producing a glass substrate of the present invention preferably provides a glass substrate containing, in mole percent, as a glass composition: 60-75% SiO2, 10-15% Al2O3, 0-5% B2O3, 0-0.1% Li2O, 0-0.1% Na2O, 0-1% K2O, 0-8% MgO, 0-10% CaO, 0-10% SrO, 0-10% BaO, 0-10% ZnO, 50-10% P2O, and 0-1% SnO2.
[0016] In the method for producing a glass substrate of the present invention, after forming a glass substrate, the glass substrate is preferably divided to obtain two or more glass substrates each having a G6 size (1.5 m×1.8 m).
[0017] The method for producing a glass substrate of the present invention is a method for producing a glass substrate by melting and shaping a glass raw material to have a strain point of 690 to 750°C and a thermal shrinkage rate of 15 ppm or less when heat-treated at 500°C for 1 hour, and containing, in mol %, 60 to 75% SiO2, 10 to 15% Al2O3, 0 to 5% B2O3, 0 to 0.1% Li2O, 0 to 0.1% Na2O, 0 to 1% K2O, 0 to 8% MgO, 0 to 10% CaO, 0 to 10% SrO, 0 to 10% BaO, 0 to 10% ZnO, 50 to 10% P2O, and 0 to 1% SnO2, and is characterized in that after shaping the glass substrate, the glass substrate is divided to obtain two or more glass substrates of G6 size (1.5 m x 1.8 m).
[0018] The method for producing a glass substrate of the present invention includes melting glass raw materials and down-draw forming the glass raw materials to produce a glass substrate having a strain point of 690 to 750° C. and a glass composition, in mole %, of SiO2 60 to 75%, Al2O3 10 to 15%, B2O3 0 to 5%, Li2O 0 to 0.1%, Na2O 0 to 0.1%, K2O 0 to 1%, MgO 0 to 8%, CaO 0 to 10%, SrO 0 to 10%, BaO 0 to 10%, ZnO 0 to 10%, and ZnO 0 to 10%. The method for producing a glass substrate containing 0-10%, P2O50-10%, and SnO20-1%, is characterized in that, during the cooling process during molding, the average cooling rate in the temperature range from (annealing point +150°C) to (annealing point -200°C) is set to 100-400°C / min, thereby obtaining a glass substrate having a thermal shrinkage rate of 15 ppm or less when heat-treated at 500°C for 1 hour and a sheet width of 3 m or more, and then dividing the glass substrate in the width direction to obtain two or more glass substrates of G6 size (1.5 m x 1.8 m).
[0019] The glass substrate of the present invention has a strain point of 690 to 750°C and a thermal shrinkage rate of 15 ppm or less when subjected to a heat treatment at 500°C for 1 hour, and is characterized by containing, in mole %, the following glass composition: 60 to 75% SiO2, 10 to 15% Al2O3, 0 to 5% B2O3, 0 to 0.1% Li2O, 0 to 0.1% Na2O, 0 to 1% K2O, 0 to 8% MgO, 0 to 10% CaO, 0 to 10% SrO, 0 to 10% BaO, 0 to 10% ZnO, 50 to 10% P2O, and 0 to 1% SnO2. Effect of the Invention
[0020] According to the present invention, it is possible to provide a method for manufacturing a glass substrate that can reduce dimensional changes during heat treatment while avoiding a shortened life of equipment. [Brief description of the drawings]
[0021] [Figure 1] FIG. 2 is an explanatory diagram for explaining a method for measuring a thermal shrinkage rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The thermal shrinkage of a glass substrate depends mainly on the strain point of the glass substrate and the cooling rate during molding. Therefore, in the present invention, by adjusting the strain point of the glass substrate to 690 to 750°C and the average cooling rate in the cooling process during molding to 100 to 400°C / min in the temperature range from (annealing point + 150°C) to (annealing point - 200°C), it is possible to obtain a glass substrate having a thermal shrinkage of 15 ppm or less when heat-treated at 500°C for 1 hour.
[0023] First, the characteristics and composition of the glass substrate will be described.
[0024] The thermal shrinkage rate when heat-treated at 500°C for 1 hour is preferably 15 ppm or less, 14.5 ppm or less, 14 ppm or less, 13.5 ppm or less, 13 ppm or less, 12.5 ppm or less, and particularly preferably 12 ppm or less. In this way, even if heat-treated in the manufacturing process of LTPS, defects such as pattern shift are unlikely to occur. If the thermal shrinkage rate is too low, the production efficiency of the glass substrate is likely to decrease. Therefore, the thermal shrinkage rate is preferably 1 ppm or more, 2 ppm or more, 3 ppm or more, 4 ppm or more, and particularly preferably 5 ppm or more.
[0025] The higher the strain point, the lower the heat shrinkage rate. The strain point is preferably 690°C or more, 695°C or more, 700°C or more, 702°C or more, 704°C or more, 705°C or more, 706°C or more, 707°C or more, 708°C or more, 709°C or more, and particularly 710°C or more. On the other hand, if the strain point is too high, the melting temperature and molding temperature become high, so that the production efficiency of the glass substrate tends to decrease, and the load on the molding equipment tends to increase. Therefore, the strain point is preferably 750°C or less, 748°C or less, 746°C or less, 744°C or less, 742°C or less, 740°C or less, 738°C or less, 736°C or less, 735°C or less, 734°C or less, 733°C or less, 732°C or less, 731°C or less, and particularly 730°C or less. The most preferred range of the strain point is 710 to 730°C.
[0026] 10 4.5 The lower the temperature in dPa·s, the less strain the molding equipment can be subjected to. 4.5The temperature at dPa·s is preferably 1300° C. or less, 1295° C. or less, 1290° C. or less, 1285° C. or less, 1280° C. or less, 1275° C. or less, and particularly preferably 1270° C. or less. 4.5 If the temperature at dPa·s is too low, the strain point cannot be designed to be high. 4.5 The temperature in dPa·s is preferably 1150°C or higher, 1170°C or higher, 1180°C or higher, 1185°C or higher, 1190°C or higher, 1195°C or higher, 1200°C or higher, 1205°C or higher, 1210°C or higher, 1215°C or higher, and particularly preferably 1220°C or higher.
[0027] In addition to the above characteristics, the glass substrate preferably has the following characteristics.
[0028] When forming into a plate shape by the overflow downdraw method or the like, devitrification resistance becomes important. Considering the forming temperature of glass containing SiO2, Al2O3, B2O3 and alkaline earth metal oxides (RO) in the glass composition, the liquidus temperature is preferably 1300°C or less, 1280°C or less, 1270°C or less, 1250°C or less, 1240°C or less, 1230°C or less, 1220°C or less, 1210°C or less, and particularly preferably 1200°C or less. In addition, the liquidus viscosity is 10 4.8 dPa s or more, 10 4.9 dPa s or more, 10 5.0 dPa s or more, 10 5.1 dPa s or more, 10 5.2 dPa s or more, especially 10 5.3 It is preferable that the viscosity is dPa·s or higher. Here, "liquidus temperature" refers to the temperature at which devitrified crystals (crystalline foreign matter) are observed in the glass when glass powder that passes through a standard sieve of 30 mesh (500 μm) and remains on the 50 mesh (300 μm) is placed in a platinum boat and held in a temperature gradient furnace set at 1100°C to 1350°C for 24 hours, and then the platinum boat is removed. "Liquidus viscosity" refers to the viscosity of glass at the liquidus temperature, measured using the platinum ball pull-up method.
[0029] The higher the Young's modulus, the less likely the glass substrate is to deform. The Young's modulus is preferably 78 GPa or more, 78.5 GPa or more, 79 GPa or more, 79.5 GPa or more, 80 GPa or more, 80.5 GPa or more, 81 GPa or more, 81.5 GPa or more, 82 GPa or more, 82.5 GPa or more, and particularly 83 GPa or more. On the other hand, a composition with a high Young's modulus tends to have poor chemical resistance. Therefore, the Young's modulus is preferably 120 GPa or less, 110 GPa or less, 100 GPa or less, 95 GPa or less, 90 GPa or less, and particularly 88 GPa or less. The "Young's modulus" refers to a value measured based on a dynamic elastic modulus measurement method (resonance method) based on JIS R1602.
[0030] The preferred upper limit of the thermal expansion coefficient is 45×10 -7 / ℃ or less, 42×10 -7 / ℃ or less, 41×10 -7 / ℃ or less, especially 40×10 -7 / ℃ or less, and the preferred lower limit is 35×10 -7 / ℃ or more, 36×10 -7 / ℃ or higher, especially 37×10 -7 / °C or more. If the thermal expansion coefficient is outside the above range, it will be inconsistent with the thermal expansion coefficient of various films (e.g., a-Si, p-Si), and problems such as film peeling and dimensional changes during heat treatment will easily occur. Note that the "thermal expansion coefficient" refers to the average thermal expansion coefficient measured in the temperature range of 30 to 380°C, and can be measured, for example, with a dilatometer.
[0031] The etching depth when immersed in a 10 mass % HF aqueous solution at room temperature for 30 minutes is preferably 20 μm or more, 22 μm or more, 25 μm or more, 27 μm or more, 28 μm or more, 29 to 50 μm, and particularly 30 to 40 μm. If the etching depth is too small, it becomes difficult to thin the glass substrate in the slimming process. The etching depth is an index of the etching rate. That is, if the etching depth is large, the etching rate becomes fast, and if the etching depth is small, the etching rate becomes slow.
[0032] The β-OH value is preferably 0.50 / mm or less, 0.45 / mm or less, 0.40 / mm or less, 0.35 / mm or less, 0.30 / mm or less, 0.25 / mm or less, 0.20 / mm or less, 0.15 / mm or less, and particularly preferably 0.10 / mm or less. By lowering the β-OH value, the strain point can be increased. Examples of methods for lowering the β-OH value include the following: (1) Select raw materials with low water content. (2) Add components (Cl, SO3, etc.) that reduce the amount of water in the glass. (3) Reduce the amount of water in the furnace atmosphere. (4) Bubble N2 in the molten glass. (5) Use a small melting furnace. (6) Increase the flow rate of the molten glass. (7) Use an electric melting method. Here, the "β-OH value" refers to a value obtained by measuring the transmittance of the glass using FT-IR and using the following formula.
[0033] β-OH value = (1 / X)log(T1 / T2) X: Glass thickness (mm) T1: Reference wavelength 3846cm -1 Transmittance (%) T2: Hydroxyl group absorption wavelength 3600cm -1 Minimum transmittance (%) near
[0034] The glass substrate of the present invention preferably contains, in mole percent, SiO2 60-75%, Al2O3 10-15%, B2O3 0-5%, Li2O 0-0.1%, Na2O 0-0.1%, K2O 0-1%, MgO 0-8%, CaO 0-10%, SrO 0-10%, BaO 0-10%, ZnO 0-10%, P2O50-10%, and SnO2 0-1% as a glass composition. The reasons for limiting the content range of each component as described above are as follows. In the explanation of the content range of each component, % means mol %.
[0035] If the SiO2 content is too low, the chemical resistance, especially the acid resistance, is likely to decrease, and the strain point is likely to decrease. On the other hand, if the SiO2 content is too high, the etching rate by hydrofluoric acid or a mixed solution of hydrofluoric acid is likely to be slow, the high-temperature viscosity is likely to be high, the melting property is likely to decrease, and further, SiO2-based crystals, especially cristobalite, are likely to precipitate, and the liquidus viscosity is likely to decrease. Therefore, the preferred upper limit content of SiO2 is 75%, 74%, 73%, 72%, 71%, 70%, and particularly 69%, and the preferred lower limit content is 60%, 61%, 62%, 62.5%, 63%, 63.5%, 64%, 64.5%, 65%, 65.5%, 66%, 66.5%, and particularly 67%. The most preferred content range is 67 to 69%.
[0036] If the content of Al2O3 is too low, the strain point is lowered, the amount of thermal contraction is increased, and the Young's modulus is decreased, so that the glass substrate is easily bent. On the other hand, if the content of Al2O3 is too high, the resistance to BHF (buffered hydrofluoric acid) is decreased, the glass surface is easily clouded, and the crack resistance is easily decreased. Furthermore, SiO2-Al2O3 crystals, especially mullite, are precipitated in the glass, so that the liquidus viscosity is easily decreased. The preferred upper limit of the content of Al2O3 is 15%, 14.5%, 14%, 13.5%, and especially 13%, and the preferred lower limit is 10%, 10.5%, 11%, 11.5%, and especially 12%. The most preferred content range is 12 to 13%.
[0037] B2O3 acts as a flux, lowers viscosity and improves melting property. It also improves BHF resistance and crack resistance, and further lowers liquidus temperature. On the other hand, if the content of B2O3 is too high, the strain point, heat resistance, and acid resistance are likely to decrease, especially the strain point. In addition, the glass is likely to undergo phase separation. The preferred upper limit of B2O3 content is 5%, 4.5%, and particularly 4%, and the preferred lower limit is 0%, 1%, 1.5%, 2%, 2.5%, 3%, and particularly more than 3%. The most preferred content range is more than 3% to 4%.
[0038] Li2O and Na2O deteriorate the properties of various films and semiconductor elements formed on the glass substrate, so it is preferable to reduce their contents to 0.1% (preferably 0.06%, 0.05%, 0.02%, and especially 0.01%). K2O causes less deterioration in the properties of various films and semiconductor elements formed on the glass substrate than Li2O and Na2O. In addition, the inclusion of a small amount of K2O has the effect of improving solubility and removing static electricity. Therefore, it is preferable to reduce the K2O content to 1% (preferably 0.5%, 0.4%, and especially 0.3%).
[0039] MgO is a component that reduces high-temperature viscosity without lowering the strain point and improves melting properties. In addition, MgO has the greatest effect of reducing density among RO (R is at least one selected from Mg, Ca, Sr, Ba, and Zn), but if introduced in excess, SiO2-based crystals, especially cristobalite, are precipitated, and the liquidus viscosity is likely to decrease. Furthermore, MgO is a component that is likely to react with BHF to form a product. This reaction product may adhere to the elements on the surface of the glass substrate or adhere to the glass substrate, thereby contaminating the elements and the glass substrate. Furthermore, impurities such as Fe2O3 may be mixed into the glass from the raw material for introducing MgO, such as dolomite, and the transmittance of the glass substrate may decrease. Therefore, the upper limit of the MgO content is preferably 8%, 7.5%, 7%, or 6.5%, particularly preferably 6%, and the lower limit of the MgO content is preferably 0%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, or 4%, particularly preferably 4.5%. The most preferable content range is 4.5 to 6%.
[0040] CaO, like MgO, is a component that reduces high-temperature viscosity without lowering the strain point and significantly improves melting property. However, if the CaO content is too high, SiO2-Al2O3-RO crystals, especially anorthite, are precipitated, the liquidus viscosity is likely to decrease, and the BHF resistance is decreased, and the reaction product may adhere to the element on the glass surface or adhere to the glass substrate, causing the element or glass substrate to become cloudy. Therefore, the preferred upper limit of CaO content is 10%, 9.5%, 9%, 8.5%, 8%, 7.5%, and especially 7%, and the preferred lower limit is 0%, 1%, 2%, 3%, 3.5%, 4%, 4.5%, and especially 5%. The most preferred content range is 5 to 7%.
[0041] SrO is a component that enhances chemical resistance and devitrification resistance, but if its proportion in the entire RO is too high, the melting property tends to decrease and the density and thermal expansion coefficient tend to increase. Therefore, the content of SrO is preferably 0 to 10%, 0 to 9%, 0 to 8%, 0 to 7%, 0 to 6%, and particularly preferably 0 to 5%.
[0042] BaO is a component that enhances chemical resistance and devitrification resistance, but if its content is too high, the density is likely to increase. In addition, since SiO2-Al2O3-B2O3-RO-based glass is generally difficult to melt, it is very important to improve meltability and reduce the defective rate due to bubbles, foreign matter, etc., from the viewpoint of supplying high-quality glass substrates inexpensively and in large quantities. However, BaO has a poor effect of enhancing meltability in RO. Therefore, the preferred upper limit of BaO content is 10%, 9%, 8%, 7%, 6%, 5%, 4.5%, 4%, and particularly 3.5%, and the preferred lower limit is 0%, 0.1%, 0.2%, 0.3%, 0.4%, and particularly 0.5%.
[0043] ZnO is a component that improves melting property and BHF resistance, but if the content is too high, the glass becomes easily devitrified, the strain point decreases, and it becomes difficult to ensure heat resistance. Therefore, the ZnO content is preferably 0 to 10%, 0 to 5%, 0 to 3%, 0 to 2%, and particularly preferably 0 to 1%.
[0044] P2O5 is a component that lowers the liquidus temperature of SiO2-Al2O3-CaO crystals (particularly anorthite) and SiO2-Al2O3 crystals (particularly mullite). However, if a large amount of P2O5 is introduced, the glass tends to undergo phase separation. Therefore, the content of P2O5 is preferably 0 to 10%, 0 to 5%, 0 to 3%, 0 to 2%, 0 to 1%, and particularly 0 to 0.1%.
[0045] SnO2 acts as a clarifier to reduce bubbles in glass. On the other hand, if the content of SnO2 is too high, devitrification crystals of SnO2 tend to occur in the glass. The upper limit of the SnO2 content is preferably 1%, 0.5%, 0.4%, and particularly 0.3%, and the lower limit of the SnO2 content is preferably 0%, 0.01%, 0.03%, and particularly 0.05%. The most preferred range is 0.05 to 0.3%.
[0046] In addition to the above components, other components may be incorporated. The total amount of other components incorporated is preferably 5% or less, 3% or less, and particularly preferably 1% or less.
[0047] ZrO2 is a component that enhances chemical durability, but if the amount of ZrO2 introduced is large, ZrSiO4 crystals are likely to occur. The upper limit of the ZrO2 content is preferably 1%, 0.5%, 0.3%, 0.2%, and particularly 0.1%, and from the viewpoint of chemical durability, it is preferable to introduce 0.001% or more. The most preferable content range is 0.001% to 0.1%. ZrO2 may be introduced from the raw material or may be introduced by elution from the refractory material.
[0048] TiO2 is a component that reduces high-temperature viscosity and improves melting property, and also improves chemical durability, but if incorporated in excess, UV transmittance is likely to decrease. The TiO2 content is preferably 3% or less, 1% or less, 0.5% or less, 0.1% or less, 0.05% or less, 0.03%, and particularly 0.01% or less. Incorporating a very small amount of TiO2 (for example, 0.0001% or more) has the effect of suppressing coloring due to UV rays. The most preferred content range is 0.0001 to 0.01%.
[0049] As2O3 and Sb2O3 are components that act as clarifiers, but because they are environmentally hazardous chemicals, it is desirable to avoid their use as much as possible. The As2O3 and Sb2O3 contents are preferably less than 0.3%, less than 0.1%, less than 0.09%, less than 0.05%, less than 0.03%, less than 0.01%, less than 0.005%, and especially less than 0.003%, respectively.
[0050] Iron is a component that is mixed in as an impurity from raw materials, but if the iron content is too high, there is a risk of ultraviolet light transmittance decreasing. If the ultraviolet light transmittance decreases, there is a risk of problems occurring in the photolithography process for producing TFTs, the process for aligning liquid crystals using ultraviolet light, and even the laser lift-off process in the plastic OLED manufacturing process. Therefore, the preferred lower limit of the iron content is 0.0001%, 0.0005%, 0.001%, and particularly 0.0015% in terms of Fe2O3, and the preferred upper limit is 0.01%, 0.009%, 0.008%, 0.007%, and particularly 0.006% in terms of Fe2O3. The most preferred content range is 0.0015% to 0.006%.
[0051] Cr2O3 is a component that is mixed in as an impurity from the raw material, but if the content of Cr2O3 is too high, when light is incident from the end face of the glass substrate and foreign body inspection inside the glass substrate is performed by scattered light, the light is difficult to transmit, and there is a risk of a problem with the foreign body inspection. In particular, when the substrate size is 730 mm x 920 mm or more, this problem is likely to occur. In addition, when the thickness of the glass substrate is small (for example, 0.5 mm or less, 0.4 mm or less, particularly 0.3 mm or less), the amount of light incident from the end face of the glass substrate is small, so it is important to regulate the content of Cr2O3. The preferred upper limit of the content of Cr2O3 is 0.001%, 0.0008%, 0.0006%, 0.0005%, particularly 0.0003%, and the preferred lower limit is 0.00001%. The most preferred content range is 0.00001 to 0.0003%.
[0052] SO3 is a component that is mixed in as an impurity from the raw materials, but if the content of SO3 is too high, bubbles called reboils are generated during melting and molding, which may cause defects in the glass. The preferred upper limit of the content of SO3 is 0.005%, 0.003%, 0.002%, and particularly 0.001%, and the preferred lower limit is 0.0001%. The most preferred content range is 0.0001% to 0.001%.
[0053] Next, a method for manufacturing a glass substrate will be described.
[0054] The glass raw material adjusted to obtain a glass substrate having the above composition and characteristics is fed to a glass melting device and melted at a temperature of about 1500 to 1650°C. The melting step in the present invention includes various steps such as clarification and stirring. In the melting step, the glass raw material is preferably electrically melted. Here, "electrical melting" refers to a melting method in which electricity is passed through glass, and the glass is heated and melted by the Joule heat generated thereby.
[0055] The molten glass is then fed to a forming device and formed into a plate shape by the down-draw method. As the down-draw method, it is preferable to adopt the overflow down-draw method. The overflow down-draw method is a method in which molten glass is made to overflow from both sides of a trough-shaped refractory having a wedge-shaped cross section, and the overflowed molten glass is joined at the lower end of the trough-shaped refractory while being drawn downward to form the glass into a plate shape. In the overflow down-draw method, the surface to be the surface of the glass substrate does not contact the trough-shaped refractory and is formed in a free surface state. For this reason, an unpolished glass substrate having good surface quality can be produced at low cost, and the glass can be easily made large and thin. The structure and material of the trough-shaped refractory used in the overflow down-draw method are not particularly limited as long as they can realize the desired dimensions and surface accuracy. In addition, the method of applying force when performing downward drawing is not particularly limited. For example, a method of drawing the glass by rotating a heat-resistant roll having a sufficiently large width in contact with the glass may be adopted, or a method of drawing the glass by contacting only the vicinity of the end face of the glass with a plurality of pairs of heat-resistant rolls may be adopted. Note that, in addition to the overflow downdraw method, for example, a slot down method or the like may also be adopted.
[0056] There is no particular limit to the width of the plate glass, but in order to obtain a plurality of glass substrates in the width direction (i.e., the direction perpendicular to the sheet drawing direction) in the dividing step described later, the width is preferably 2 m or more, 2.2 m or more, 2.4 m or more, 2.6 m or more, 2.8 m or more, and particularly 3 m or more. On the other hand, if the width of the plate glass is too large, the forming device tends to become too large and the life of the forming device tends to be shortened. Therefore, the width of the plate glass is preferably 4 m or less, 3.5 m or less, and particularly 3.2 m or less.
[0057] Next, the plate glass is fed to an annealing furnace and cooled. The cooling rate is directly related to the thermal shrinkage rate of the resulting glass substrate, and therefore must be strictly controlled. Specifically, in order to reduce the thermal shrinkage rate of the glass substrate, the average cooling rate in the temperature range from (annealing point +150°C) to (annealing point -200°C) is preferably 400°C / min or less, 390°C / min or less, 380°C / min or less, 370°C / min or less, 360°C / min or less, or 350°C / min or less. On the other hand, if the average cooling rate is too slow, the production efficiency tends to decrease. Therefore, the average cooling rate in the temperature range from (annealing point +150°C) to (annealing point -200°C) is preferably 100°C / min or more, 150°C / min or more, 200°C / min or more, and particularly 250°C / min or more. The cooling rate can be adjusted by adjusting the power of the heater in the glass conveying direction. Specifically, a plurality of heaters that can be adjusted separately may be provided in the glass conveying direction, and the output of each heater may be adjusted. In addition, in order to reduce the in-plane variation in the thermal shrinkage rate of the glass substrate, it is preferable that the temperature is controlled so that the variation in the cooling rate in the sheet width direction is small. Specifically, a plurality of heaters that can be adjusted separately may be provided in the sheet width direction, and the output of each heater may be adjusted. Furthermore, from the viewpoint of reducing the thermal shrinkage rate, the longer the annealing furnace, the more preferable it is, specifically, the length is preferably 2 m or more, 3 m or more, 4 m or more, 5 m or more, 6 m or more, 7 m or more, 8 m or more, 9 m or more, and particularly 10 m or more. On the other hand, if the annealing furnace is made longer, the glass melting device and the forming furnace must be installed at a higher position, which may result in restrictions on the facility design. In addition, the glass hanging down from the forming device becomes too heavy and difficult to hold. Specifically, the length of the annealing furnace is preferably 30 m or less, 25 m or less, 22 m or less, 20 m or less, 18 m or less, 16 m or less, and particularly 15 m or less.
[0058] The thus-formed plate-like glass is cut to a predetermined length to obtain a glass substrate (mother glass substrate). Furthermore, the obtained glass substrate can be divided in the width direction to obtain a plurality of glass substrates. For example, if a glass substrate (3m×1.8m glass substrate) is prepared by cutting a plate-like glass having a plate width of 3m to a length of 1.8m, two glass substrates having a G6 size (1.5m×1.8m) can be obtained, and similarly, if a glass substrate having a plate width of 2.6m×1.1m is used, two glass substrates having a G5 size (1.2m×1.0m to 1.3m×1.1m) can be obtained. Similarly, if a glass substrate having a plate width of 2.19m×0.92m is used, three glass substrates having a G4.5 size (0.73m×0.92m) can be obtained. By forming a glass substrate having a large plate width in this manner and dividing the glass substrate into a plurality of glass substrates, it is possible to improve production efficiency. Therefore, even if the average cooling rate is slowed down to reduce the thermal shrinkage rate of the glass substrate as described above, the production efficiency can be maintained. After cutting the glass substrate, various chemical or mechanical processes may be performed as necessary.
[0059] The thickness of the glass substrate is not particularly limited, but in order to facilitate weight reduction of the device, it is preferably 0.5 mm or less, 0.4 mm or less, 0.35 mm or less, and particularly 0.3 mm or less. On the other hand, if the thickness is too small, the glass substrate is easily bent. Therefore, it is preferable that the thickness of the glass substrate is 0.001 mm or more, and particularly 0.005 mm or more. The thickness can be adjusted by the flow rate and sheet drawing speed during glass production. EXAMPLES
[0060] The present invention will be described in detail below based on examples. Note that the following examples are merely illustrative and the present invention is not limited to the following examples.
[0061] Table 1 shows examples of the present invention (samples A to C, F to H) and comparative examples (samples D, E, I).
[0062] [Table 1]
[0063] First, silica sand, aluminum oxide, anhydrous boric acid, calcium carbonate, strontium nitrate, barium nitrate, stannic oxide, strontium chloride, and barium chloride were mixed together to obtain the composition shown in Table 1.
[0064] Next, the glass raw materials were fed into an electric melting furnace not using burner combustion and melted, and then in a fining tank and an adjusting tank, the molten glass was clarified and homogenized, and its viscosity was adjusted to a value suitable for molding.
[0065] The molten glass was then fed to an overflow downdraw forming device, formed into a plate, and then slowly cooled to the cooling rate shown in Table 1, and cut to produce a glass substrate with a thickness of 0.5 mm, a width of 3 m, and a length of 1.8 m. This glass substrate was then divided to obtain two glass substrates of G6 size (1.5 m x 1.8 m) with a thickness of 0.5 mm. The molten glass leaving the melting furnace was fed to the forming device while in contact with only platinum or a platinum alloy. The β-OH value, density, thermal expansion coefficient, Young's modulus, strain point, annealing point, 10 4.5 The temperature, liquidus viscosity and thermal shrinkage in dPa·s were evaluated.
[0066] The β-OH value was calculated as described above.
[0067] The density is a value measured by the well-known Archimedes method.
[0068] The thermal expansion coefficient is the average value measured by a dilatometer in the temperature range of 30 to 380°C. is the coefficient of thermal expansion.
[0069] Young's modulus was measured by the dynamic elastic modulus measurement method (resonance method) based on JIS R1602. value.
[0070] The strain point and annealing point are values measured based on the method of ASTM C336.
[0071] High temperature viscosity 10 4.5 The temperature in dPa·s was measured using the platinum ball pulling method.
[0072] The liquidus viscosity is a value obtained by measuring the viscosity of glass at the liquidus temperature by a platinum ball pull-up method.
[0073] The heat shrinkage rate was measured by the method described above.
[0074] Samples A to C and F to H had a strain point of 750°C or less and a slow cooling rate of 400°C / min or less, so the thermal shrinkage was low at 15 ppm or less. In addition, because the strain points of samples A to C and F to H were 750°C or less, it is believed that the load on the molding equipment is low. On the other hand, samples D, E, and I had a strain point of 750°C or less, but a fast cooling rate of 460°C / min or more, so the thermal shrinkage was high at 16 ppm or more. EXAMPLES
[0075] Table 2 shows examples of the present invention (samples 1 to 8) and a comparative example (sample 9).
[0076] [Table 2]
[0077] Samples 1 to 8 shown in Table 2 were prepared in the same manner as in Example 1 and evaluated.
[0078] Samples 1 to 8 had a low thermal shrinkage of 14 ppm or less because the strain point was 750°C or less and the cooling rate was slow at 400°C / min or less. In addition, since the strain point of Samples 1 to 8 was 750°C or less, it is considered that the load on the molding equipment is low. On the other hand, Sample 9 had a low strain point of less than 690°C, so the thermal shrinkage was high at 20 ppm.
Claims
1. The method for producing a glass substrate having a strain point of 710 to 750°C is characterized in that, in a cooling process during the forming process, an average cooling rate in the temperature range of (annealing point + 150°C) to (annealing point - 200°C) is set to 100 to 400°C / min, thereby obtaining a glass substrate having a thermal shrinkage rate of 15 ppm or less when heat-treated at 500°C for 1 hour.
2. 2. The method for producing a glass substrate according to claim 1, wherein the glass substrate is formed by an overflow downdraw method.
3. 3. The method for producing a glass substrate according to claim 1, wherein the glass substrate has a width of 3 m or more.
4. The glass composition is, in mol%, SiO 2 60-75%, Al 2 O 3 10-15%, B 2 O 3 0-5%, Li 2 O 0-0.1%, Na 2 O 0 to 0.1%, K 2 O 0-1%, MgO 0-8%, CaO 0-10%, SrO 0-10%, BaO 0-10%, ZnO 0-10%, P 2 O 5 0-10%, SnO 2 4. The method for producing a glass substrate according to claim 1, wherein the glass substrate contains 0 to 1% of arsenic.
5. 5. The method for producing a glass substrate according to claim 1, further comprising the steps of: forming the glass substrate; dividing the glass substrate into two or more glass substrates each having a G6 size (1.5 m×1.8 m).
6. The glass raw materials are melted and molded to produce a glass having a strain point of 710 to 750°C and a glass composition of, in mol%, SiO 2 60-75%, Al 2 O 3 10-15%, B 2 O 3 0-5%, Li 2 O 0-0.1%, Na 2 O 0 to 0.1%, K 2 O 0-1%, MgO 0-8%, CaO 0-10%, SrO 0-10%, BaO 0-10%, ZnO 0-10%, P 2 O 5 0-10%, SnO 2 The present invention relates to a method for producing a glass substrate containing 0 to 1% of arsenic, the method being characterized in that, in a cooling process during molding, an average cooling rate in the temperature range of (annealing point + 150°C) to (annealing point - 200°C) is set to 100 to 400°C / min to obtain a glass substrate having a thermal shrinkage rate of 15 ppm or less when heat-treated at 500°C for 1 hour, and then the glass substrate is divided to obtain two or more glass substrates of G6 size (1.5 m x 1.8 m).
7. The glass raw material is melted and down-draw molded to obtain a glass having a strain point of 710 to 750°C and a glass composition of, in mole percent, SiO 2 60-75%, Al 2 O 3 10-15%, B 2 O 3 0-5%, Li 2 O 0-0.1%, Na 2 O 0 to 0.1%, K 2 O 0-1%, MgO 0-8%, CaO 0-10%, SrO 0-10%, BaO 0-10%, ZnO 0-10%, P 2 O 5 0-10%, SnO 2 The present invention relates to a method for producing a glass substrate containing 0 to 1% of arsenic, the method being characterized in that, in a cooling process during molding, an average cooling rate within a temperature range from (annealing point + 150°C) to (annealing point - 200°C) is set to 100 to 400°C / min to obtain a glass substrate having a thermal shrinkage rate of 15 ppm or less when heat-treated at 500°C for 1 hour and a plate width of 3 m or more, and the glass substrate is then divided in the width direction to obtain two or more glass substrates of G6 size (1.5 m x 1.8 m).
Citation Information
Patent Citations
Method for producing glass substrate
JP2011020864A
Production method for glass belt
JP2013133246A
Glass plate and method for producing glass plate
JP2013230963A
Method of manufacturing glass substrate and cooler
JP2014070000A
Manufacturing method of glass substrate
JP2016011235A